Knowledge and Practice on Infection Prevention among Medical Doctors Working at a COVID-19 Unit of a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Infectious Diseases, 2022)
Background: IPC knowledge and practice can shield HCWs from being infected or even worse.Objective: The study assessed the knowledge and practice of COVID-19 prevention among doctors in Bangladesh.Methodology: This cross-sectional study conducted from July to September 2020 recruited 210 medical doctors assigned to COVID-19 unit of BSMMU. Data were collected in two phases where 133 doctors completed both phases. Descriptive analysis and binary logistic regression were performed for statistical analysis.Results: About 1.5% of the doctors were infected with COVID-19 following their duty. 90% of doctors correctly identified indications for performing hand hygiene. Knowledge and compliance to PPE was high. The doctors having formal training on IPC were more likely to have an adequate practice of infection prevention measures.Conclusion: Knowledge and practice of IPC measures were better among doctors having prior training before entering their duty that led to less infection rate.Bangladesh Journal of Infectious Diseases December 2021;8(2):57-63